Nutritional Status of school-going adolescents in urban and rural areas in the Duhok District (Journal of Pharmaceutical Negative Results, 2022)
The assessment of nutritional status as a part of the school health component can serve as a screening tool to identify adolescents who need nutritional intervention and to prevent further deterioration in their nutritional status with reducing the risk of poor school performance.The study aimed to assess and compare anthropometric indices among school adolescents in the rural and urban areas in the Duhok district. Anthropometric indices including height, weight, and Body mass index were used to estimate the adolescent nutritional status. The data were analyzed by using WHO Anthro Plus software.A cross-sectional study was conducted to understand the malnutrition scenario among the rural school children of 6-15 years age group and interplay of different sociodemographic factors contributing to it. Anthropometric data were analysed using WHO Anthro Plus version 1.0.4 software for assessing the growth of the children and by using appropriate statistical methods. A cross-sectional study was conducted to understand the malnutrition scenario among the rural school children of 6-15 years age group and interplay of different sociodemographic factors contributing to it. Anthropometric data were analysed using WHO Anthro Plus version 1.0.4 software for assessing the growth of the children and by using appropriate statistical methods A total of 650 students were assessed. About 65.7% normal BMI, while the rest distributed as 10.8% obese, 17.4% overweight, 5.4% thin, and 0.8% severe thinness. The obtained results show that there is no significant statistical association between BMI and sex, age, socioeconomic status of the families and residency.